A realização fonética do /s/ pós-vocálico nos municípios de Boca do Acre, Lábrea e Tapauá - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
This research fits in the perspective of Pluridimensional Dialectology, proposed by Radtke & Thun (1996). We investigated the variants of the / S / post-vocalic in the speech of the inhabitants of three villages belonging to the micro-region of Purus, the State of Amazonas: Boca do Acre, and Lábrea Tapauá. For this study, we considered the variables gender and age in order to observe the influence of these factors in the selection of variants by speaker. Likewise, there was a review in the light of phonological theories, namely the Generative Theory of Classical Distinctive Traits proposed in The Sound Pattern of English (SPE), Chomsky and Halle (1968) and the Theory of the syllable, for the best understanding of the phenomenon in this language system. In this study, we investigated 18 informants living in the localities under investigation, distributed as follows: 6 informants in each locality, being a man and a woman in each of three age groups (18-35 years old, 36-55 years old and 56 years old on). The informants were selected obeying pre-established criteria: being illiterate, being natives of the locality under investigation and having parents who are also natives of that locality, besides not having been away from the city for more than a third part of their lives. The study was conducted following guidelines already established by the geolinguistic method: a) the interviews were conducted through responses to the phonetic-phonological questionnaire (PPQ) and free conversations of up to 30 minutes, both recorded digitally; b) the graphematic transcription of all interviews were done, both the data collected by the PPQ and the ones collected in free speech, constituting a database for future dialectology researches; c) the phonetic transcription of the words collected through the PPQ was done. These data resulted in 51 phonetic letters and 13contextual phonetic letters, that indicate the use of the alveolar variant as the most frequent in the area. However, the phoneme analysis in specific contexts showed that variants are conditioned by certain contexts, of which we cite the post-alveolar variant that is particularly preferred by the medial context before occlusive [t]; the aspirated variant, conditioned by anterior context, the lateral and the nasal; and deletion that occurs often in end context, when the / S / is a plural morpheme. To the prevalence of the alveolar variant over the others the historical factor is assigned, once the region was populated by migrants from the northeast state of Maranhão and Ceará, the rubber tappers in the heyday of the latex. As for the specificities of each phoneme in context, we found explanation in phonological theories, especially on the sonority scale proposed by Jaspersen (1904 cited in Hooper 1976). It was noticed that the noisier the next segment is, the less weak the phoneme under investigation becomes, tending to weakness (aspiration); the less noisy the next segment, the stronger the phoneme under investigation is, favoring the post-alveolar variant. The analysis by social factors, in turn, reveals as conservative variant the alveolar pronunciation, while the aspirated variant seems to be more innovative. The analysis also reveals the location of Tapauá as the most conservative and the location of Lábrea as the most innovative.
Keywords: Dialetologia Pluridimensional; Fonética; Fonologia; Linguística; Linguagem e línguas; Pluridimensional Dialectology; Phonology; LINGUÍSTICA, LETRAS E ARTES: LETRAS